Detection of Metallo-β-lactamase Carbapenemase Genes in Carbapenem-Resistant Pseudomonas Strains from Bloodstream Infections - Yılmaz Yücel, Fadime; Köksal Çakırlar, Fatma (Cerrahpaşa Medical Journal, 2024)
Objective: Metallo-β-lactamase (MBL) production is one of the most important mechanisms causing the development of resistance to carbapenems. In this study, we intended to investigate the presence of Verona integron mediated (VIM)-, imipenemase (IPM)-, and imipenemase (NDM)-type MBL in Pseudomonas strains isolated from blood cultures in Cerrahpaşa Medical School Hospital. Methods: In our study, a total of 48 ‘carbapenem-resistant/intermediate Pseudomonas strains were isolated from blood samples of patients with bacteremia over 4 years. For all strains, screening for the presence of “MBL genes” was performed by “multiplex PCR,” and “phenotypic MBL E-test” was used. Results: The VIM-type MBL gene was detected in 3 isolates (1 Pseudomonas putida and 2 Pseudomonas aeruginosa). Imipenemase- and NDM-type MBL genes were not detected in any of the strains. Specificity and sensitivity of MBL E-test were determined to be 100% according to multiplex PCR results. Conclusion: In our study, VIM-type MBL gene was first shown in Pseudomonas strains at our hospital. Detection of carbapenemase genes will contribute to the implementation of infection control measures that will reduce their spread and the rational use of antibiotics. Cite this article as: Yılmaz Yücel F, Köksal Çakırlar F. Detection of metallo-β-lactamase carbapenemase genes in carbapenemresistant pseudomonas strains from bloodstream infections. Cerrahpaşa Med J. 2024;48(3):207-211.